2021
DOI: 10.1002/cre2.393
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization of a power‐driven water flosser during regular use. A proof‐of‐principle study

Abstract: Objectives: The present proof-of-principle study assessed whether daily use of a power-driven water flosser (Sonicare AirFloss; SAF) leads to bacterial colonization in the nozzle and/or the device, resulting in contaminated water-jet.Material and Methods: In five participants, saliva samples at baseline and waterjet samples of devices used daily with bottled water for 3 weeks (test) were collected.Additionally, water-jet samples from devices used daily with bottled water extraorally for 3 weeks (positive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In general, all studies included herein reported that PDICTs are indeed safe to use. Nevertheless, recent reports from our group have indicated that liquid‐based PDICTs are unavoidably colonized by oral bacteria, which can be transmitted via the water jet (Bertl, Edlund Johansson, Bruckmann et al, 2021 ; Bertl et al, 2022 ). Contamination of a specific liquid‐based PDICT with Streptococcus mutans was found in >95% of the samples, while periodontal pathogens were detected in 19%–56% of the samples (Bertl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, all studies included herein reported that PDICTs are indeed safe to use. Nevertheless, recent reports from our group have indicated that liquid‐based PDICTs are unavoidably colonized by oral bacteria, which can be transmitted via the water jet (Bertl, Edlund Johansson, Bruckmann et al, 2021 ; Bertl et al, 2022 ). Contamination of a specific liquid‐based PDICT with Streptococcus mutans was found in >95% of the samples, while periodontal pathogens were detected in 19%–56% of the samples (Bertl et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%